Apakah Liberalisasi Pendidikan Tinggi Meminggirkan Perguruan Tinggi Nasional? - Awan S. Dewanta (Unisia, 2006)
In recent decades today it happens the changing of world economy orientation from manufacturing and sercive-based economies to knowledge based-economies. The main factor of the national economy building capacity is not only physical capital but also knowledge and technology. The science and technology become influenced factor for developing a nation. The higher education denotes institution that can produce the research of science, technology and educated human resources. In term of the copy right research products, the institutions and the universities in Indonesia are behind in the eastern Asian and Asean countries, for instances South Korea, Taiwan, and Singapore. These countries have shown the qualities in developing science and they become the competitor of  advanced countries.